ANALISIS JUMLAH KROMOSOM PADA TRIPLOIDISASI IKAN MAS (Cyprinus carpio Linn) RAS PUNTEN DENGAN LAMA PERENDAMAN KEJUT SUHU PANAS YANG BERBEDA - Rahmad Hendro Susilo; Farikhah Farikhah; Andi Rahmad Rahim (Universitas Muhammadiyah Gresik, 2018)
Goldfish (Cyprinus carpio Linn) punten breeds is a type of freshwater fish that has greatpotential in terms of quality and quantity. Seed production from generation to generation hasdecreased quality. An alternative effort was made to maintain the seed quality of geneticengineering with triploidization process using heat shock treatment. The heat shock can preventpolar body II from splitting on eggs during cleavage of meiosis II level resulting in 3Nchromosome or sterile fish. The purpose of this research is to analyze chromosome number intriploidization process of punten breeds fish and to analyze the effect of temperature shockduration on hatching rate of goldfish (Cyprinus carpio Linn) Punten Breeds. This research wasdescriptive research with 2 treatments and 3 replications in each treatment that was heat shocktreatment 40 ºC at minute 2 after fertilization with difference of heat shock duration 1,5 minutes(treatment A) and shock time temperature 2 minutes (treatment B). The parameters observedwere triploid success, hatching rate, survival rate, and growth of of goldfish (Cyprinus carpioLinn) Punten Breeds, analyzed by T-test with 95% confidence interval. The result of heat shockduration of 1.5 minutes showed the percentage of triploid fish 53,57% and shock timetemperature 2 minute 43,64%. The result of T-test of both treatments had no significant effect onall observation parameters but had varied relationship that was enough and inversely related toall observation parameters